Keandalan Waduk Tenayan Dalam Memenuhi Kebutuhan Air Bersih Areal Perkantoran Tenayan Raya - Aprian Harza; Siswanto Siswanto; Trimaijon Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Tenayan reservoir is a reservoir that built to supply demands of clean water to office areas of Tenayan Raya. Office areas of Tenayan Raya is an area that is planned to be the center of Pekanbaru city government. The central government which had previously been at the center of the city is already too crowded and this displacement can encourage equitable development to the suburbs. It required the analysis of the reliability of reservoir Tenayan. Reliability is known with simulating the availability of water for 20 years with the water demands of the office. The data what used to calculate the availability of water using Pekanbaru station rainfall data for the period 1994 - 2013. The availability of water is calculated by the method of Mock period of 10 daily. Demands of clean water for office simulated for 10 liter/second, 20 liter/second, 40 liter/second, 80 liter/second and 100 liter/second. With the effective capacity of the reservoir Tenayan is ± 840.528 m3, so the results from this analysis is known that the reservoir that able to supply 100 % the water’s demands of office are in simulated extraction of waters for 10 liter/second and 20 liter/second. Reservoir reliability at simulated extraction for 40 liter/second is 95,56%, reservoir reliability at simulated extraction for 80 liter/second is 92,22% and reservoir reliability at simulated extraction for 100 liter/second is 90,97%.Keywords: Tenayan reservoir, storage capacity, water balance